Penegakan Hukum Dalam Hal Pelanggaran Lalu Lintas Terhadap Pengendara Ojek Online yang Menggunakan Telepon - Zainal Fatah (Kajian Hasil Penelitian Hukum, 2019)
The existence of an online motorcycle taxi that uses the telephone to work is a form of violation of Law Number 22 Year 2009 Regarding Traffic and Road Transportation. Drivers must be careful when using the phone while driving, because when driving while using a telephone, the driver can be punished by the police, and could endanger other drivers. This research is a normative legal research that is a library research using a normative juridical approach, besides using supporting data that is conducting interviews with SatlantasSleman Police as a resource and conducting interviews with online motorcycle taxi drivers as respondents of this study. After an analysis of all of them, it can be concluded that the online motorcycle taxi drivers who put the phone on the motorcycle are considered to violate traffic, because of obvious reasons the driver uses the phone, namely to work or look for orders. Interpretation of Law Number 22 Year 2009 Regarding Traffic and Road Transportation in article 106 states that motorists are prohibited from using the telephone while driving. Although according to the Sleman Yogyakarta Police, they stated that they did not violate traffic because there were no clear rules forbidding placing the telephone in a vehicle.